Long-term Cross-reactivity Against Nonvaccine Human Papillomavirus Types 31 and 45 After 2- or 3-Dose Schedules of the AS04-Adjuvanted Human HPV-16/18 Vaccine. (3rd February 2019) - Folschweiller, Nicolas; Behre, Ulrich; Dionne, Marc; Durando, Paolo; Esposito, Susanna; Ferguson, Linda; Ferguson, Murdo; Hillemanns, Peter; McNeil, Shelly A; Peters, Klaus; Ramjattan, Brian; Schwarz, Tino F; et al.
Abstract: This analysis focused on long-term cross-reactive immunogenicity against nonvaccine human papillomavirus (HPV) types 31 and 45 following 2 doses of AS04-adjuvanted HPV-16/18 vaccine in girls aged 9–14 years or following 3 doses in women aged 15–25 years, for up to 3 years (HPV-070 study) and up to 5 years (HPV-048 study) after the first vaccination. Both schedules elicited antibodies against HPV-31 and HPV-45 up to 5 years after first dose. The antibody concentration was similar in young girls as compared to women. Specific CD4 + T-cell and B-cell responses to HPV-31 and HPV-45 at month 36 were similar across groups. Clinical trials registration: NCT01381575 and NCT00541970. Abstract : The AS04-adjuvanted human papillomavirus type 16/18 (HPV-16/18) vaccine showed sustained cross-reactivity against nonvaccine HPV types 31 and 45 for up to 5 years, whether administered as a 2-dose schedule in girls aged 9–14 years or as a 3-dose schedule in women aged 15–25 years.